Case report of pigmented villonodular synovitis arising from the calcaneocuboid joint in a 12 year old male. Issue 1 (March 2015) - Duncan, Nicholas; Rajan, Rohan
Highlights Pigmented villonodular synovitis (PVNS) of the calcaneocuboid joint is rare. There is a high risk of recurrence following excision of PVNS. Magnetic resonance imaging is the modality of choice for investigation.